Incubadora Sol a Sol: premissas para o desenvolvimento de empreendimentos inovadores no Alto Solimões - Amazonas - Ferreira, Cleyton Cid da Siilva (Brasil, 2021)
This research is about the creation of a Solidarity Economy Entrepreneur Incubator, in the Amazon, in middle region of Alto Solimões. Incubators are entities that promote innovative ventures that aim to provide support so that they can develop ideas and transform them into successful enterprises. In turn, Solidarity Economy is the set of guiding principles that guide small and micro enterprises, aiming to get them out of isolation. Therefore, Solidarity Economy Entrepreneur Incubator is the space that offers advice and exchanges of knowledge, giving visibility to social groups excluded from the formal market. Thus, a question emerged that guides this research, seeking to know what are the requirements for the structure and functioning of an incubator, aiming to prepare a proposal for the structure and functioning of a popular technological incubator to develop third-sector enterprises/projects in Alto Solimões. The research was carried out through a literature review on the subject, contacts via email and WhatsApp, electronic form in the Google Forms tool and data collection. After analysing the results, a survey points to the creation of the Sol A Sol Incubator - Alto Solimões Solidarity Economy Entrepreneur Incubator. Therefore, it led to considering the incubator in 3 fundamental points: the premises for the business incubator based on 4 dimensions; the incubator model, being Solidarity Economy and, finally, the three-phase incubation method.